Psychology themes and variations - Weiten, Wayne 1950- (Thomson/Wadsworth, 2007)
Offers students a survey of psychology with three goals: to show both the unity and diversity of psychology's subject matter; to illuminate the process of research and its intimate link to application; and, to make the text challenging to think about and easy to learn from. This text includes empiricism and theoretical diversity.